CITES and Domestic Economy in Indonesia: The Efforts of Indonesian Government to Change The Lamakera Fishers Commodity in Implementing The 2013 CITES Convention - Iyan Septiyana (Journal of Indonesian Social Sciences and Humanities, 2017)
Indonesia is a maritime country where most of the people work as fishers. The number of fishers in Indonesia is around 1.4 million people. Lamakera is a village on Solor Island, and part of East Flores Regency, East Nusa Tenggara Province. The geographical condition which is the strait makes the Lamakera sea area visited by various types of fish, including whales and manta rays. In 2012 researchers proposed a moratorium of International trade of Manta rays gills to IUCN that agreed on the international convention in the CITES framework. Indonesia, as part of the CITES, binds their selves to the convention and must implement it. In another side, Manta is the primary commodity for Lamakera fishers. By using liberal-institutionalism perspective on international relations, this article will describe how the efforts of the Indonesian government change the livelihood of local people concerning the implementation of CITES 2013.